ANALYSIS OF THE INDIVIDUAL PROCESS OF SOCIAL AND PSYCHOLOGICAL ADAPTATION OF SEVERELY WOUNDED COMBATANTS (Psychology Travelogs, 2024)
The article outlines the problem of providing quality psychological assistance to severely wounded combatants in Ukraine who return from combat. Given that a significant number of servicemen face not only physical injuries but also serious psychological trauma after demobilization, the process of their social and psychological adaptation is studied. The analysis covers several stages of adaptation, during which veterans often face various difficulties. The author emphasizes the importance of a comprehensive approach to adaptation, which includes not only physical but also emotional support. Particular attention is paid to the role of social support from family, friends and community, which can significantly facilitate the integration of severely wounded combatants into society. The complexity of the period of returning to peaceful life in the context of restoring social roles and adaptation mechanisms is described. It is noted that individual and social factors have a significant impact on the ability of veterans to adapt to new living conditions. Individual psychological factors, such as personal resilience, self-esteem, and the ability to introspect, determine internal changes that affect the effectiveness of stress coping and adaptation. Emotional aspects, such as anxiety, depression, and post-traumatic stress disorder, can significantly complicate this process, emphasizing the importance of professional psychological support. It is emphasized that the process of psycho-emotional rehabilitation for severely wounded combatants should be implemented according to an individual program that should take into account the uniqueness of each individual, his or her previous experience and the nature of the injuries received. The author highlights modern methods of psychological support, such as cognitive training, neurorehabilitation and art therapy, which provide the necessary basis for the successful integration of veterans into society. The forms of support provided by the state are considered.
Keywords: adaptation; rehabilitation; support; rights; veterans; combatants